Uruguayan EFL Teachers’ Experiences of the Role of SEL in Diverse Classrooms - Burgin, Ximena; Daniel, Mayra; Coli, Sheila (Institut Agama Islam Negeri Palopo, 2023)
The impact of COVID-19 exacerbated the need to integrate social emotional learning (SEL) for equitable instruction in English as a Foreign Language Classrooms (EFL). This case study explored the integration of SEL in Uruguayan classrooms and its influence on educational practice. Thirteen teachers from public and private schools completed a Cultural Awareness Survey and answered open-ended questions before, during, and after viewing a professional development video on SEL. Findings document that participants recognized the diversity in their classrooms and the relationship between cultural values and interpersonal respect. All participants indicated that their pedagogy focuses on SEL activities, but their responses did not reflect the integration of SEL concepts into the EFL curriculum. Keywords: Culturally responsive instruction; English as a foreign language; social emotional learning; Uruguayan Teachers